Investigation on a smart nanocarrier with a mesoporous magnetic core and thermo-responsive shell for co-delivery of doxorubicin and curcumin: a new approach towards combination therapy of cancer. Issue 46 (31st May 2017) - Asghar, Khushnuma; Qasim, Mohd; Dharmapuri, Gangappa; Das, Dibakar
Abstract : A novel and smart MIO-P(NIPAM-MAm) nanocomposite has been prepared for combinational delivery of Dox and Cur for cancer treatment. Abstract : In this work, we report on the synthesis and characterization of a novel and smart nanocarrier with a mesoporous magnetic core and thermo-responsive shell for co-delivery of hydrophilic doxorubicin (Dox) and hydrophobic curcumin (Cur) as a combinational therapy for cancer treatment. The P(NIPAM-MAm) coated mesoporous Fe3 O4 (MIO-P(NIPAM-MAm)) nanocomposite was prepared by in situ cross linked polymerization of NIPAM and MAm on the surface of pre-synthesized mesoporous Fe3 O4 nanoparticles (MIO NPs) in the presence of an oxidizer and cross linker. MIO NPs were synthesised by co-precipitation method using CTAB as the sacrificial soft template. Different characterization techniques have been used to study the physicochemical properties of MIO NPs and the MIO-P(NIPAM-MAm) nanocomposite. Particle sizes of the MIO-P(NIPAM-MAm) nanocomposite estimated by TEM were found to be in between 200–500 nm. VSM results show MIO and MIO-P(NIPAM-MAm) nanocomposites to be superparamagnetic in nature. MIO-P(NIPAM-MAm) nanocomposites exhibited a lower critical solution temperature (LCST) of 41 °C, which is suitable for controlled drug delivery applications unlike pure PNIPAM based nanocarriers. The encapsulation efficiency of Dox and Cur were found to be 96% and 90% respectively. Temperature dependent release studies from MIO-P(NIPAM-MAm)-Cur-Dox indicated a slower release of drugs (both Dox and Cur) below LCST and a sustained release above LCST. Different mathematical models (such as zero order, first order, Higuchi and Korsmeyer–Peppas) were used to fit the experimental release profiles of both drugs. MTT assays on normal and HeLa cells demonstrated the non-toxic nature of the MIO-P(NIPAM-MAm) nanocomposite. The co-loaded MIO-P(NIPAM-MAm)-Cur-Dox nanocomposite exhibited higher in vitro anti-cancer activity compared to free Dox, free Cur, and a free Dox + free Cur mixture. Such a co-loaded smart delivery system could have potential for controlled and targeted drug delivery in cancer diagnosis.